Characteristics of Geological Anomalies Shown on Seismic Time Sections - Xiaobing GENG (CT Lilun yu yingyong yanjiu)
With the rapid development of three-dimensional (3D) seismic exploration technology in recent years, its application has demonstrated significant advantages in interpreting the form and structure of underground coal seams, particularly in identifying geological anomalies and delineating their extent. Common geological anomalies such as goafs, collapse columns, coal seam outcrops, magmatic rock intrusions, fire zones, coal seam scouring zones, and coal seam bifurcations were identified through the distinct characteristics observed in seismic time sections, yielding highly accurate geological interpretations.